Crumpled reduced graphene oxide–amine–titanium dioxide nanocomposites for simultaneous carbon dioxide adsorption and photoreduction. Issue 16 (22nd June 2016) - Nie, Yao; Wang, Wei-Ning; Jiang, Yi; Fortner, John; Biswas, Pratim
Abstract : Crumpled reduced graphene oxide–amine–titanium dioxide nanocomposites (CGOATI) for simultaneous CO2 adsorption and photoreduction were synthesized by an one-step aerosol approach. Abstract : Crumpled reduced graphene oxide–amine–titanium dioxide nanocomposites (CGOATI) were synthesized by an one-step aerosol technique to enable simultaneous carbon dioxide (CO2 ) adsorption and photoreduction. Graphene oxide (GO), chemically modified by ethylenediamine (EDA), was crumpled using an aerosol process, encapsulating TiO2 nanoparticles to form core–shell nanostructures. The three-dimensional (3D) structure largely prevented the crumpled graphene nanosheets from restacking by minimizing π–π interactions, thus enhancing the stability of the catalyst by retaining its higher surface area. A combination of a 20% mass percentage of TiO2 /GO, a 15 : 1 mass ratio of EDA/GO in precursor solution, and a 200 °C synthesis temperature led to the highest CO yield (65 μmol g −1 h −1, with an apparent quantum efficiency of 0.0094%), which was two-fold higher than that of crumpled reduced GO–TiO2 (CGOTI) and four-fold higher than that of TiO2 alone. The enhancement of CO2 photoreduction was attributed to higher CO2 adsorption on the amine-functionalized reduced-GO (r-GO) surface and the strong electron trapping capability of r-GO. The insertion of EDA on r-GO nanosheets, the adsorption of CO2 by amine groups, and the photoreduction of the adsorbed CO2 were confirmed by FTIR and XPS spectra analysis. The r-GO nanosheets themselves were simultaneously photoreduced during CO2 photoreduction. Raman spectroscopy and conductivity measurements showed that photoreduced r-GO had a higher electronic conductivity than thermally reduced r-GO, and led to more effective CO2 photoreduction. This study offers new insights into the design and fabrication of graphene-based photocatalysts for CO2 photoreduction.